Analisis Performa State Snapshot Transfers (SST) Tipe Blocking (Rsync) dan Non Blocking (Xtrabackup-V2) pada MariaDB Galera Cluster - Gilang Ramadhan; Mahendra Data; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Reliability and availability of database server becomes the crucial things of application system. There are so many researches that have been done in order to increase the reliabilty and availability of database server. The example is using database replication mechanism. MariaDB is one of DBMS that has a replication mechanism through MariaDB Galera Cluster application. MariaDB Galera Cluster has several methods called State Snapshot transfer (SST) which is used for replication process, namely Rsync, Xtrabackup, Xtrabackup-v2, and Mysqldump. This study focused to compare the performance of Rsync method and Xtrabackup-v2 method. The experimental results show that both methods have a similar performance. Number of nodes in a cluster can affect the performance of cluster. Cluster with two nodes would be more vulnerable to become an error if one of the node becomes has failed. Therefore, the minimum number of nodes on a cluster is three on condition that there is just one node that failed. This experiment also results another conclusion that SST method that used and number of nodes can affect the replication times. Rsync method has a shorter duration of replication compared to the Xtrabackup-v2.